Cytokine profile in childhood-onset systemic lupus erythematosus: a cross-sectional and longitudinal study - Cavalcanti,A. (2017)
Childhood-onset systemic lupus erythematosus (cSLE) exhibits an aggressive clinical phenotype and severe complications. This could be due to a pro-inflammatory cytokine milieu. Therefore, we determined plasma levels of Th1 (IL-2, IFN-γ, TNF), Th2 (IL-4), Th17 (IL-17A, IL-6), and Treg (IL-10) cytokines in a cohort of cSLE patients and healthy controls, and we evaluated the association between these cytokines and disease activity. We conducted a cross-sectional study with 51 cSLE patients from two pediatric rheumatology services. Ten cSLE patients participated in a longitudinal follow-up study. Blood samples were collected from the same patient during active and inactive disease. Disease activity was evaluated according to SLE Disease Activity Index 2000 (SLEDAI-2K). Cytokines levels were measured by cytometric bead array technique. cSLE patients had higher IL-6 (P<0.001) and IL-10 (P<0.001) levels than healthy controls. Patients with active disease had higher IL-6 and IL-10 levels than patients with inactive disease (P=0.001 and P=0.014, respectively) and the control group (both P<0.001). IL-6 (P=0.022), IL-10 (P=0.013), and IL-17A (P=0.041) levels were significantly higher during active than inactive disease. Linear regression analysis revealed IL-6 (P=0.002, 95%CI=0.006-0.025) and IL-10 (P=0.01 95%CI=0.021-0.150) as independent factors for increased SLEDAI-2K. IL-6, IL-10, and IL-17A are candidate biomarkers for disease activity in cSLE patients. This is the first longitudinal study to support their pivotal role in the pathogenesis of the disease.